Factors Influencing International Students' Choice of an Education Destination-A Correspondence Analysis - Shanka, Tekle; Quintal, Vanessa; Taylor, Ruth (Routledge, 2006)
A correspondence analysis technique was employed to elicit information from international students pertaining to their choice of study destination. A survey of international students at a major Australian university revealed that the proximity of the city to the students' home countries, in addition to safety, the educational quality/variety, etc. were the main reason for choosing this city for their study. Other reasons for choice included cost of living and tuition fees. A correspondence analysis (CA) data analysis technique was employed resulting in a two-dimension solution on a safety/proximity and quality/ familiarity continuum was considered acceptable. The two-dimension solution with a significant chi-square (X2) value accounted for 93 % of the total variance explained. Results were discussed and future research directions were indicated. Copyright (c) by The Haworth Press, Inc. All rights reserved.